Upaya Meningkatkan Hasil Belajar Matematika Siswa dengan Menggunakan Alat Peraga Papan Pintar - Nur Indriani, Arina; Siti Aisah (Metakognisi, 2024)
Classroom Action Research is an activity that is compulsory to be carried out in lectures in addition to being included in one aspect of assessment during lectures, Classroom Action Research (PTK) is also a program that provides opportunities for students to learn to make journals. Especially education students are given the opportunity to become teacher partners in the learning process Through this program, students have a role to provide better learning to schools and creativity. The numeracy ability of SDN Gunung Batu 1 students, especially grade 4, is very lacking because there are still many students who think that learning related to numeracy is very difficult and boring. This is because numeracy is based on formulas and calculations. Assistance is carried out by providing material related to operations integers using smart boards. Smart boards are used in addition and subtraction materials with the aim to assist 4th graders in understanding integer operation materials. There is a difference before mentoring and after mentoring where there is an increase in knowledge that is more related to integer material. The increase is influenced by two factors, namely internal and external factors.